2016
DOI: 10.1016/j.jseaes.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Crustal structure across the post-spreading magmatic ridge of the East Sub-basin in the South China Sea: Tectonic significance

Abstract: The 140-km wide last phase of opening of the South China Sea (SCS) corresponds to a N145° direction of spreading with rift features identified on swath bathymetric data trending N055° (Sibuet et al., 2016). These N055° seafloor spreading features of the East Sub-basin are cut across by a post-spreading volcanic ridge oriented approximately E-W in its western part (Zhenbei-Huangyan seamounts chain). The knowledge of the deep crustal structure beneath this volcanic ridge is essential to elucidate not only the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The 41 OBS data processing includes instrument relocation and band‐pass filtering (3–12 Hz; Zhang et al, ). As examples of OBS recordings, picking phases, PmP phases, ray tracing, and travel times simulation are published for Profile P4 in He et al (); other examples will not be displayed in this paper. P wave velocity models along these four profiles were first derived by forward modeling using the Rayinvr code of Zelt and Smith ().…”
Section: Single‐channel Reflection and Wide‐angle Seismic Refraction mentioning
confidence: 99%
“…The 41 OBS data processing includes instrument relocation and band‐pass filtering (3–12 Hz; Zhang et al, ). As examples of OBS recordings, picking phases, PmP phases, ray tracing, and travel times simulation are published for Profile P4 in He et al (); other examples will not be displayed in this paper. P wave velocity models along these four profiles were first derived by forward modeling using the Rayinvr code of Zelt and Smith ().…”
Section: Single‐channel Reflection and Wide‐angle Seismic Refraction mentioning
confidence: 99%
“…The main material composition within a seamount is generally igneous rocks, whose geophysics feature is obviously different from the submarine sediment or mud volcano [ Davies and Stewart , ; Chiu et al ., ; Chen et al ., ; He et al ., ]. Therefore, we identified and selected seamounts in the study area according to the following criteria: (1) rising from the seafloor to more than 0.1 km in height [ Kim and Wessel , ], (2) having high external amplitude seismic reflections, (3) having low amplitude and chaotic internal seismic reflections, (4) having obvious uplift of the adjacent strata at the flanks [ Zhang et al ., ], (5) having higher positive free‐air gravity anomalies [ Tomoda and Fujimoto , ; Wessel et al ., ; Kim and Wessel , ; He et al ., ], and (6) having higher (positive or negative) magnetic anomalies [ Heirtzler Amp and Hadley , ]. Criteria 1–5 were necessary for each seamount, but criterion 6 was not rigorously required for identification due to the geomagnetic polarity reversal in the Earth's history [ Hildebrand and Staudigel , ].…”
Section: Data and The Seamount Identification Processmentioning
confidence: 99%
“…Controversy in the relict ridge location (Barckhausen et al, ; Briais et al, ; Li et al, ; Sibuet et al, ; Taylor & Hayes, ; Zhao et al, ) prevents the recognization of spreading scenarios. Recent OBS surveys revealed a low P wave velocity zone in the upper crust across the rift valley of the SWRR (Zhang et al, ) and the seamount chain of the East Subbasin (He et al, ; white circles in Figures , , and ). Previous studies have found that relict ridges typically exhibit low velocities in the upper crust because of the existence of extrusive high‐porosity rocks, volcaniclastic sediments, and shallow faults (Grevemeyer et al, ; Weigel & Grevemeyer, ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, core samples, seismic profiles, multibeam bathymetry, free‐air anomalies (FAAs) of gravity (Sandwell et al, ), magnetic anomaly data (Ishihara & Kisimoto, ), P wave velocity (Zhang et al, ; He et al, ), and earthquake focal mechanisms were used.…”
Section: Methodsmentioning
confidence: 99%